The outcome of surgical management of post-infectious hydrocephalus with multiple intraventricular septations - Mohamed Mohsen Amen; Mohamed Badran; Ahmed Zaher; Amr Farid Khalil; Ibrahim Abdelaal; Mahmoud Saad (Egyptian Journal of Neurosurgery, 2023)
Abstract Objectives Post-infection hydrocephalus with multiple intraventricular septations is a complex issue in neurosurgery, with multiple treatment options available. The authors reviewed the results of neuroendoscopic cyst wall fenestration for managing this disease. Materials and Methods Medical records of 76 patients with post-infection hydrocephalus and multiple intraventricular septations who underwent endoscopic treatment were collected and analyzed. Results The patient group consisted of 40 males (52.6%) and 36 females (47.4%), with a mean age of 22.36 months (range: 4–132 months). Bacterial meningitis was the most common cause of hydrocephalus with multiple intraventricular septations in 37 patients (48.6%), while 24 patients had post-shunt infection (31.6%) that was complicated with multiloculated hydrocephalus. After confirming clearance of CSF infection, all patients underwent ventriculoscopic cyst fenestration and insertion of a ventriculoperitoneal shunt to create a single communicating system drained by one ventricular catheter. Fifty-five patients underwent De novo shunt implantation, while 20 patients required shunt revision. Endoscopy reduced the shunt revision rate from 3.4 per year before fenestration to 0.4 per year after fenestration. During the mean follow-up period of 7.7 months (range: 1–20 months), complications were reported in 13 patients (17.1%), including CSF leakage in eight (10.5%), VPS malfunction in five (6.5%), and two deaths (2.6%). Conclusion The authors concluded that neuroendoscopic fenestration with the aid of CSF drainage by intraventricular catheter is an effective treatment for managing multiloculated post-infection hydrocephalus with much lower rates of morbidity and mortality than traditional procedures.